소포림프종의 진단 및 치료의 최신 동향 - 송가영; Ga-young Song; 양덕환; Deok-hwan Yang (The Korean journal of medicine, 2023)
Follicular lymphoma (FL) is the third most common subtype of non-Hodgkin lymphoma in Korea. Patients with FL generally present with asymptomatic lymphadenopathy, which may wax and wane for years and have indolent disease course. Most patients with FL have advanced-stage disease at diagnosis and less than 20% of patients with FL have stage I/II disease. Radiation therapy is generally accepted with the treatment of choice for limited-stage FL and results in 60-80% of 10-year overall survival rates. Patients with advanced- stage FL do not require an immediate treatment unless they have symptomatic disease, compromised end organ function, B symptoms, or cytopenia. The initial treatment of advanced-stage FL recommends rituximab-containing immunochemotherapy followed by 2 years of maintenance with rituximab, or bendamustine plus rituximab is a preferred choice because of superior progression- free survival with less toxicity than other rituximab-containing immunochemotherapy. For patients with relapsed or refractory FL, there are many options ranging from anti-CD20 monoclonal antibody alone to a combination with lenalidomide and chemotherapy or autologous stem cell transplantation. In addition, the novel approaches for relapsed or refractory FL have been applied with phosphoinositide 3-kinase inhibitor, Bruton’s tyrosine kinase inhibitor, enhancer of zeste homolog 2 inhibitor, anti-CD19 chimeric antigen receptor T-cell therapy and bispecific antibodies. (Korean J Med 2023;98:231-240)